Digital media, fantasy sport and the transformation of the contemporary field of sport. Issue 4 (1st October 2016) - Schirato, Tony
ABSTRACT: This article is concerned with how and why the commercial imperatives, logics, values and technologies of the contemporary commercial media are transforming the field of sport. In order to exemplify this last point, I shall look at the ways in which fantasy sport, a relatively recent phenomenon that is predominantly tied to and operated through various forms of digital media, is transforming what Jonathan Crary (1998) would call the 'visual regime' of the field of sport. I shall start with two sets of (brief) contextualising introductions: the first will provide a very general history of the development of the sport–mass media nexus; the second look at the relatively recent phenomenon of fantasy sport, and then describe and analyse how digitally mediated fantasy sport produces an entirely different way of looking at the things of sport and by extension transforms the traditional visual regime of sports' spectatorship.